2018
DOI: 10.1111/nph.15515
|View full text |Cite
|
Sign up to set email alerts
|

Cistrans controls and regulatory novelty accompanying allopolyploidization

Abstract: Summary Allopolyploidy is a prevalent process in plants, having important physiological, ecological and evolutionary consequences. Transcriptomic responses to genomic merger and doubling have been demonstrated in many allopolyploid systems, encompassing a diversity of phenomena including homoeolog expression bias, genome dominance, expression‐level dominance and revamping of co‐expression networks. Notwithstanding the foregoing, there remains a need to develop a conceptual framework that will stimulate a deepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 120 publications
(154 reference statements)
2
65
0
Order By: Relevance
“…Similarly, it has been shown that the dominant genome can be targeted by less silencing in comparison to the parental level, while the recessive genome retains the parental level of silencing (reviewed in Bird et al , 2018). The ‘TE model’ of subgenome‐specific bias and its influence on cis–trans interactions and homoeologue expression are discussed in a recent paper by Hu & Wendel (2019). In addition to the ‘TE model’, a transcription factor model is also highlighted as a strong candidate in shaping the fate of the divergent subgenomes (Hu & Wendel, 2019).…”
Section: Epigenetic Relevance Of Hybridization and Whole Genome Doublingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been shown that the dominant genome can be targeted by less silencing in comparison to the parental level, while the recessive genome retains the parental level of silencing (reviewed in Bird et al , 2018). The ‘TE model’ of subgenome‐specific bias and its influence on cis–trans interactions and homoeologue expression are discussed in a recent paper by Hu & Wendel (2019). In addition to the ‘TE model’, a transcription factor model is also highlighted as a strong candidate in shaping the fate of the divergent subgenomes (Hu & Wendel, 2019).…”
Section: Epigenetic Relevance Of Hybridization and Whole Genome Doublingmentioning
confidence: 99%
“…The ‘TE model’ of subgenome‐specific bias and its influence on cis–trans interactions and homoeologue expression are discussed in a recent paper by Hu & Wendel (2019). In addition to the ‘TE model’, a transcription factor model is also highlighted as a strong candidate in shaping the fate of the divergent subgenomes (Hu & Wendel, 2019).…”
Section: Epigenetic Relevance Of Hybridization and Whole Genome Doublingmentioning
confidence: 99%
“…Enrichment of promoter motifs in these 87 DEGs (Additional File 6) is consistent with a model in which transcriptional regulation from the AABB genomes may differentially regulate DD genes during later stages of grain development. Such emergent patterns of cis-trans interactions in polyploid genomes have been modelled (Bottani et al 2018;Hu and Wendel 2018) .…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of homoeolog expression is particularly interesting, given the various patterns of duplicate gene expression possible in polyploid species (reviewed in [12]), the interactions among homoeologs in a gene network context [6,14], and the phenomenon of unbalanced homoeolog expression bias together with its potential long-term consequences for fractionation [72][73][74]. A number of previous studies have explored the bioinformatics of homoeolog expression profiling [68][69][70][71]; however, both the fundamental issue of read ambiguity and the downstream inferences regarding polyploid expression evolution have not been addressed.…”
Section: Bioinformatic Choices Can Strongly Affect the Interpretationmentioning
confidence: 99%
“…Polyploidy in plants is far more prevalent than once thought, acting historically and more recently to shape the genomes of all angiosperms and most other groups of plants [8][9][10][11]. One realization that has emerged in the last decade is that polyploidy is accompanied by massive transcriptomic responses, as reviewed [12][13][14]. These responses are many and varied, including biased homoeolog expression, conditionspecific differential homoeolog usage, transgressive expression levels, and expression level dominance.…”
Section: Introductionmentioning
confidence: 99%